Recycling tenofovir in second-line antiretroviral treatment with dolutegravir: outcomes and viral load trajectories to 72 weeks - Keene, CM; Cassidy, T; Zhao, Y; Griesel, R; Jackson, A; Sayed, K; Omar, Z; Hill, A; Ngwenya, O; Van Zyl, G; Flowers, T; Goemaere, E; et al. (Lippincott, Williams and Wilkins, 2023)
Background: Recycling tenofovir and lamivudine/emtricitabine with dolutegravir (TLD) after failure of non-nucleoside transcriptase inhibitor first-line antiretroviral therapy is more tolerable and scalable than dolutegravir plus optimized nucleoside reverse transcriptase inhibitors. Studies have demonstrated TLD's efficacy as second line, but long-term follow-up is limited. Methods: ARTIST is a single arm, prospective, interventional study conducted in Khayelitsha, South Africa, which switched 62 adults with 2 viral loads >1000 copies/mL from tenofovir, lamivudine/emtricitabine, and an non-nucleoside transcriptase inhibitor to TLD. We report efficacy to 72 weeks and, in a post hoc analysis, evaluated viral load trajectories of individuals with viremic episodes. Results: Virologic suppression was 86% [95% confidence interval (CI) 74 to 93], 74% (95% CI: 61 to 84), and 75% (95% CI: 63 to 86) <50 copies/mL and 95%, 84%, and 77% <400 copies/mL at week 24, 48, and 72, respectively, with 89% (50/56) resistant (Stanford score ≥15) to tenofovir and/or lamivudine preswitch. No participants developed integrase-inhibitor resistance. Of the 20 participants not suppressed at week 24 and/or 48, 2 developed virologic failure, 1 switched regimen (adverse event), 2 were lost to follow-up, 1 missed the visit, 1 transferred out, 9 resuppressed <50 copies/mL with enhanced adherence counseling, and 4 remained viremic (3 with <200 copies/mL) at week 72. Conclusions: Recycling NRTIs with dolutegravir was effective for most participants to 72 weeks. Most with viremia did not develop virologic failure and subsequently suppressed with enhanced adherence counseling or continued to have low-level viremia. No integrase-inhibitor resistance was detected despite low-level viremia in a minority of participants.